Method for preparing titanium carbonitride-based metal ceramic formed part by using binder jet 3D printing technology
By using titanium carbonitride-based cermet powder and binder jet printing technology, combined with the regulation of materials and processes, the preparation problem of complex-shaped cermet molded parts in 3D printing is solved, and efficient and low-cost preparation is achieved. The molded parts have excellent mechanical properties and dimensional accuracy.
Patent Information
- Application Number
- CN202411812130.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to efficiently prepare high-performance cermet molded parts of complex shapes, especially in 3D printing technology, which have defects such as thermal cracks, metastable phase, high temperature warpage and anisotropy.
Titanium nitride-based cermet powder is used to prepare titanium nitride-based cermet molded parts through binder jet printing technology, combining the regulation of the material system, curing and sintering densification process parameters to achieve efficient preparation of molded parts.
The high-efficiency and low-cost preparation of complex-shaped cermet molded parts is achieved. The molded parts have a relative density of more than 98%, Rockwell hardness of 86 to 92HRA, a lateral fracture strength of 1800N/mm2 to 2200N/mm2, and the length and dimensional error is controlled below 0.15mm.
Smart Images

Figure BDA0005180794770000151 
Figure BDA0005180794770000152
Abstract
Description
Technical Field
[0001] The present invention relates to the field of powder metallurgy and additive manufacturing. Specifically, the present invention relates to a titanium carbonitride-based metal ceramic powder that can be used for 3D printing and a preparation method thereof. The present invention also relates to a binder jet printing method for preparing a titanium carbonitride-based metal ceramic molded part from the titanium carbonitride-based metal ceramic powder and the prepared titanium carbonitride-based metal ceramic molded part. Background Art
[0002] Cermets are a type of heterogeneous composite material formed by metal or alloy and one or more ceramic phases. They not only maintain the high strength, high hardness, wear resistance, high temperature resistance and oxidation resistance of ceramics, but also have the toughness and plasticity of metals. At present, according to the types of non-metallic ceramic phases in cermets, cermets can be mainly divided into four types: oxide-based, boride-based, carbide-based and carbonitride-based cermets. Among them, among carbonitride-based cermets, the representative titanium carbonitride (Ti(C,N))-based cermet is a new type of cermet developed on the basis of titanium carbide (TiC)-based cermets. Due to its high strength and hardness, excellent high temperature resistance and wear resistance, good toughness and thermal conductivity, and low density, it has been increasingly valued by the scientific and industrial communities, and has been well applied in many processing fields.
[0003] 3D printing (additive manufacturing) is a new generation of "revolutionary" manufacturing technology. Compared with traditional powder metallurgy methods, 3D printing has unique technical advantages such as high material utilization, high manufacturing flexibility, small processing allowance, few structural design constraints, near-net forming of complex structural molded parts, and rapid response to structural design changes, which makes it possible to manufacture high-performance complex-shaped cemented carbide parts. However, due to the high melting point and high brittleness of cemented carbide, it is difficult to avoid defects such as thermal cracks, metastable phases, high-temperature warping, and anisotropy during the 3D printing preparation process using traditional 3D printing methods such as laser selective melting (SLM), electron beam selective melting (EBM), and fused filament fabrication (FFF).
[0004] Binder jet 3D printing (BJ3D printing) is a new type of low-cost and high-speed additive manufacturing technology. It selectively bonds metal powder with the aid of a binder to obtain a three-dimensional printed blank, which is then post-processed by degreasing and sintering to obtain a dense metal part. BJ3D printing technology has the following advantages: (1) It is not limited to the type of metal powder raw materials and can also effectively combine functional gradient materials; (2) Binder jet molding technology only requires printing the binder (the binder accounts for a small part of the total molded part volume), so it has a high build rate; (3) The printing speed is fast and can be used for large-scale production with low overall production costs; (4) The molding process does not require atmosphere protection and high temperature environment, which can avoid problems such as high temperature oxidation, warping, and residual stress; (5) The unprinted powder around the molded part has high recyclability; (6) The green molded part can effectively eliminate some internal defects in the printing process during subsequent heating and densification processes; (7) By adjusting the sintering temperature and sintering time, different densities and porosities can be controlled to a certain extent.
[0005] BJ3D printing technology combines the characteristics of powder metallurgy and additive manufacturing. Compared with powder metallurgy, it reduces mold investment and can prepare parts with complex shapes. Compared with other 3D printing technologies, there is no input of high-energy beam heat source, and there are no problems such as rapid cooling, residual stress, anisotropy and oxidation during the printing process.
[0006] However, how to use BJ3D printing technology to prepare high-performance metal ceramic molded parts with complex shapes, opening up a new way for the efficient and low-cost preparation of high-performance metal ceramics, especially complex-shaped metal ceramic molded parts, has not yet been solved in the existing technology, and it has important theoretical and application value. Summary of the invention
[0007] Purpose of the Invention
[0008] In view of the problems existing in the prior art described in the above background technology section, the object of the present invention is to provide a titanium carbonitride-based metal ceramic powder that can be used for 3D printing and a preparation method thereof; the present invention also aims to provide a binder jet printing method for preparing titanium carbonitride-based metal ceramic molded parts from the titanium carbonitride-based metal ceramic powder and the prepared titanium carbonitride-based metal ceramic molded parts.
[0009] Technical Solution
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] Scheme 1: A titanium carbonitride-based metal ceramic powder that can be used for 3D printing, wherein the titanium carbonitride-based metal ceramic powder comprises, based on the total weight of the metal ceramic powder:
[0012] about 70 wt % to about 90 wt % of a hard phase, the hard phase comprising a Ti(C,N) matrix and a tungsten carbide (WC) reinforcement phase;
[0013] about 9 to about 27 weight percent nickel (Ni) and / or cobalt (Co) binder phase, and
[0014] from about 1 to about 3 weight % of an inhibitor,
[0015] The particle size of the titanium carbonitride-based cermet powder is in the range of about 5 to about 45 μm.
[0016] Option 2: The titanium carbonitride-based metal ceramic powder according to Option 1 above, wherein the titanium carbonitride-based metal ceramic powder comprises as the hard phase, based on the total weight of the metal ceramic powder:
[0017] about 55 to about 65 weight percent Ti(C,N) matrix, and
[0018] About 15 to about 25 wt. % WC reinforcement phase.
[0019] Option 3: The titanium carbonitride-based metal ceramic powder according to Option 1 or 2 above, wherein the titanium carbonitride-based metal ceramic powder contains about 10 to about 20 weight % of the Ni and / or Co binding phase based on the total weight of the metal ceramic powder.
[0020] Scheme 4: The titanium carbonitride-based metal ceramic powder according to any one of Schemes 1 to 3 above, wherein the Ti(C,N) matrix comprises Ti(C x ,N 1-x ) matrix, wherein x is from about 0.1 to about 0.9.
[0021] Option 5: The titanium carbonitride-based metal ceramic powder according to any one of the above options 1 to 4, wherein the inhibitor comprises tantalum carbide (TaC), titanium carbide (TiC), chromium carbide (Cr3C2) and / or vanadium carbide (VC).
[0022] Scheme 6: A method for preparing a titanium carbonitride-based metal ceramic powder according to any one of Schemes 1 to 5 above, wherein the method comprises:
[0023] Step 1: providing a mixed powder, and optionally subjecting the mixed powder to a grinding process, wherein
[0024] The mixed powder comprises, based on the total weight of the mixed powder:
[0025] about 70 to about 90 weight percent of a hard phase powder, the hard phase powder comprising Ti(C,N) powder and WC powder,
[0026] about 9 to about 27 weight percent Ni and / or Co powder, and
[0027] about 1 to about 3 weight percent inhibitor powder;
[0028] Step 2: mixing the mixed powder with a granulating agent in an amount of about 80 to about 100 g per kilogram of the mixed powder, and granulating the mixed powder into a granular material having a particle size of less than about 150 μm;
[0029] Step 3: raising the temperature of the granules obtained in step 2 to about 280° C. to about 450° C. at a heating rate of, for example, not more than about 3° C. per minute, maintaining the temperature to remove the granulating agent, and then pre-alloying the granules from which the granulating agent has been removed at a temperature of about 700 to about 1000° C. for about 15 to about 30 minutes; and
[0030] Step 4: crushing and classifying the pre-alloyed particles obtained in step 3 to obtain the titanium carbonitride-based cermet powder having a particle size ranging from about 5 to about 45 μm.
[0031] Scheme 7: The preparation method according to Scheme 6 above, wherein the mixed powder in step 1 comprises, based on the total weight of the mixed powder:
[0032] about 55 wt % to about 65 wt % Ti(C,N) powder,
[0033] about 15 to about 25 weight percent WC powder,
[0034] about 10 to about 20 wt. % Ni and / or Co powder, and
[0035] About 1 to about 3 weight percent inhibitor powder.
[0036] Scheme 8: The preparation method according to Scheme 6 or 7 above, wherein the Ti(C,N) powder has a Fisher particle size in the range of about 1.50 to about 2.50 μm.
[0037] Scheme 9: The preparation method according to any one of schemes 6 to 8 above, wherein the WC powder has a particle size range of about 0.7 to about 1.3 μm.
[0038] Scheme 10: The preparation method according to any one of schemes 6 to 9 above, wherein the Ni powder has a particle size range of about 2.2 to about 2.8 μm.
[0039] Scheme 11: The preparation method according to any one of schemes 6 to 10 above, wherein the Co powder has a particle size range of about 0.8 to about 1.0 μm.
[0040] Scheme 12: The preparation method according to any one of schemes 6 to 11 above, wherein the inhibitor powder has a particle size range of about 1.0 to about 1.5 μm.
[0041] Scheme 13: The preparation method according to any one of Schemes 6 to 12 above, wherein the granulating agent comprises paraffin and / or polyethylene glycol.
[0042] Scheme 14: A binder jet printing method for preparing a titanium carbonitride-based metal ceramic molded part using the titanium carbonitride-based metal ceramic powder according to any one of Schemes 1 to 5 above or the titanium carbonitride-based metal ceramic powder prepared by the preparation method according to any one of Schemes 6 to 13 above, wherein the method comprises:
[0043] Step a: using a binder jet printing process, jet-printing the titanium carbonitride-based metal ceramic powder binder to obtain a printed blank, wherein the powder thickness is about 0.05 to about 0.2
[0044] mm range;
[0045] Step b: curing the printed blank obtained in step a at a temperature of about 80 to about 200° C. for about 3 to about 5 hours to obtain a cured part;
[0046] Step c: The solidified part obtained in step b is kept at a temperature of at least about 350° C. to remove the binder, and is subjected to pressure liquid phase sintering at a temperature of about 1350 to about 1500° C. and a pressure of at least about 6 MPa for about 30 to about 90 minutes to obtain the titanium carbonitride-based cermet molded part.
[0047] Scheme 15: The binder jet printing method according to Scheme 14, wherein the binder jet printing process of step a uses a resinous organic binder having a viscosity in the range of about 8 to about 15 cps and a binder having a viscosity in the range of about 0.7 to about 1.5 mg / cm 2 The amount of binder sprayed.
[0048] Scheme 16: A titanium carbonitride-based metal ceramic molded part prepared by the binder jet printing method according to Scheme 14 or 15 above, wherein the molded part has one or more of the following properties:
[0049] The relative density is about 98% or more.
[0050] Rockwell hardness of about 86 to about 92 HRA,
[0051] About 1800N / mm 2 To about 2200N / mm 2 The transverse rupture strength, and
[0052] The length dimension error is less than 0.15mm for every 100mm length.
[0053] Technical Effects
[0054] The present invention proposes a titanium carbonitride-based metal ceramic powder that can be used for 3D printing, and uses a binder jet printing technology to form it into a metal ceramic molded part, which solves the molding problem of complex-shaped metal ceramic molded parts, and prepares metal ceramic special-shaped parts with excellent mechanical properties by adjusting the material system, curing and sintering densification process parameters. The problem of difficult processing and preparation of complex-shaped metal ceramic molded parts is solved, and a technical breakthrough in the field of metal ceramics and binder jetting is achieved.
[0055] The binder jet 3D printing method of titanium carbonitride-based cermet provided by the present invention is a combination of additive manufacturing technology and powder metallurgy process, which can solve the problem of difficult molding and post-processing of complex-shaped titanium carbonitride-based cermet molded parts. The obtained titanium carbonitride-based cermet molded parts still have a large relative density (about 98% or more), high hardness (Rockwell hardness of about 86 to about 92 HRA), and a large transverse rupture strength (about 1800N / mm) under the specified dimensional error (length dimensional error of about 0.15mm or less per 100mm length). 2 To about 2200N / mm 2 ) and other excellent mechanical properties.
[0056] The formula of the titanium carbonitride-based metal ceramic powder of the present invention can obtain metal ceramic materials and parts with different mechanical property ranges by adjusting the ratio of the hard phase and the binding phase, so as to match various performance and application requirements. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without paying creative work belong to the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on normal conditions.
[0058] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. The term "about" used in the present invention means that the modified numeral can fluctuate within the range of ±20%, ±15%, ±10%, ±5% or ±2% of the numeral. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in the present invention.
[0059] According to a first aspect of the present invention, the present invention provides a titanium carbonitride-based metal ceramic powder that can be used for 3D printing.
[0060] The titanium carbonitride-based cermet powder according to the first aspect of the present invention comprises, based on the total weight of the cermet powder:
[0061] about 70 wt % to about 90 wt % of a hard phase, the hard phase comprising a Ti(C,N) matrix and a WC reinforcement phase;
[0062] about 9 to about 27 weight percent Ni and / or Co binder phase, and
[0063] from about 1 to about 3 weight % of an inhibitor,
[0064] The particle size of the titanium carbonitride-based cermet powder is in the range of about 5 to about 45 μm.
[0065] In the titanium carbonitride-based metal ceramic powder according to the first aspect of the present invention, the content of the hard phase should be in the range of about 70 wt % to about 90 wt %, such as about 75 wt %, about 80 wt % or about 85 wt %. The weight proportion of the hard phase should not be too high, such as not exceeding about 90 wt %, otherwise the molded part prepared from the ceramic powder is too brittle; nor should it be too low, such as not less than about 70 wt %, otherwise the hardness of the molded part prepared from the ceramic powder is too low.
[0066] In an exemplary embodiment, the weight ratio of the Ti(C,N) matrix as a part of the hard phase contained in the titanium carbonitride-based cermet powder according to the first aspect of the present invention is about 55 to about 65 weight %, for example, about 60 weight %, and the weight ratio of the WC reinforcement phase as a part of the hard phase is about 15 to about 25 weight %, for example, about 20 weight %. Here, the ratio of the Ti(C,N) matrix to the WC reinforcement phase should not be lower than about 55:25, otherwise the high temperature wear resistance and oxidation resistance of the cermet may be poor, and should not be higher than about 65:15, otherwise the bending strength of the cermet molded part may be too low.
[0067] In the titanium carbonitride-based cermet powder according to the first aspect of the present invention, the ratio of carbon element to nitrogen element in the Ti(C,N) matrix is not particularly limited. However, in some preferred embodiments, the Ti(C,N) matrix comprises Ti(C x ,N 1-x ) matrix, wherein x is from about 0.1 to about 0.9. For example, in some particularly preferred embodiments, Ti(C 0.3 N 0.7 )、Ti(C 0.4 N 0.6 )、Ti(C 0.5 N 0.5 )、Ti(C 0.6 N 0.4 ) or Ti(C 0.7 N 0.3 ) and other matrices as the Ti(C,N) matrix.
[0068] In the titanium carbonitride-based metal ceramic powder according to the first aspect of the present invention, the weight proportion of Ni and / or Co as a binder phase should be in the range of about 9 to about 27 weight %, for example, about 12 weight %, about 15 weight %, about 18 weight %, 21 weight % or about 24 weight %, and particularly preferably in the range of about 10 to about 20 weight %. The weight proportion of Ni and / or Co here should not exceed about 27 weight %, otherwise the hardness of the molded part prepared from the ceramic powder may be too low; nor should it be less than about 9 weight %, otherwise the molded part prepared from the ceramic powder may be too brittle.
[0069] In the titanium carbonitride-based cermet powder according to the first aspect of the present invention, the ratio of Ni and Co in the binder phase is not particularly limited, as long as the sum of their weight percentages is within the above range. For example, in some preferred embodiments, the binder phase used includes the following combination:
[0070] about 8 wt% Co + about 10 wt% Ni;
[0071] about 5 wt% Co + about 10 wt% Ni;
[0072] About 10 wt% Ni;
[0073] about 10 wt % Co + about 10 wt % Ni; or
[0074] About 8 wt% Co + about 8 wt% Ni.
[0075] In the titanium carbonitride-based metal ceramic powder according to the first aspect of the present invention, the inhibitor is used to inhibit grain growth during the sintering and densification process of preparing the titanium carbonitride-based metal ceramic powder. As the inhibitor, some transition metal carbides can be used. For example, in some preferred embodiments of the present invention, the inhibitor used includes one or more of TaC, TiC, Cr3C2 and VC.
[0076] The weight proportion of the inhibitor used should be in the range of about 1 to about 3 weight %, such as about 1.5 weight %, about 2 weight %, or about 2.5 weight %. Here, the weight proportion of the inhibitor should not exceed about 3 weight %, otherwise it may cause the brittleness of the molded part prepared from the powder to be too large; nor should it be less than about 1 weight %, otherwise it may cause the grain growth during the sintering process of the ceramic powder, thereby reducing the mechanical properties of the metal ceramic molded part prepared from the metal ceramic powder.
[0077] The particle size of the titanium carbonitride-based metal ceramic powder according to the first aspect of the present invention should be in the range of about 5 to about 45 μm. Here, the particle size of the metal ceramic powder should not exceed about 45 μm, otherwise the density of the blank formed by the powder by binder injection 3D molding may be insufficient; nor should it be less than about 5 μm, otherwise the fluidity of the powder is affected, thereby making it impossible to smoothly spread the ceramic powder by binder 3D printing.
[0078] According to a second aspect of the present invention, the present invention provides a method for preparing the titanium carbonitride-based metal ceramic powder according to the first aspect of the present invention. The specific and preferred features described for the titanium carbonitride-based metal ceramic powder in the first aspect of the present invention are also applicable to the second aspect of the present invention.
[0079] The preparation method according to the second aspect of the present invention comprises the following steps 1 to 4.
[0080] The step 1 comprises providing a mixed powder, and optionally subjecting the mixed powder to a grinding process, wherein the mixed powder comprises, based on the total weight of the mixed powder:
[0081] about 70 to about 90 weight percent of a hard phase powder, the hard phase powder comprising Ti(C,N) powder and WC powder,
[0082] about 9 to about 27 weight percent Ni and / or Co powder, and
[0083] About 1 to about 3 weight percent inhibitor powder.
[0084] In the above step 1, the mixed powder preferably comprises about 55 to about 65 wt % of Ti(C,N) powder, about 15 to about 25 wt % of WC powder, about 10 to about 20 wt % of Ni and / or Co powder, and about 1 to about 3 wt % of inhibitor powder based on the total weight of the mixed powder.
[0085] In the above step 1, the purpose of the grinding treatment is to make the Ti(C,N) powder, WC powder, Ni and / or Co powder and inhibitor powder forming the mixed powder more fully and evenly mixed together. For example, in a preferred embodiment of the present invention, the mixed powder can be subjected to a ball milling wet mixing treatment, and then the wet milled powder is dried and sieved, wherein the ball milling medium used is preferably alcohol, the grinding ball is a cemented carbide ball with a diameter ranging from about 8 to about 10 mm, the ball-to-material ratio (weight ratio) can be set to about 7:1, and the ball milling time can be set to about 30 hours.
[0086] In some exemplary embodiments of step 1 above, the Ti(C,N) powder preferably has a Fisher particle size in the range of about 1.50 to about 2.50 μm, for example, about 1.75 μm, about 2.00 μm, or about 2.25 μm; the WC powder preferably has a particle size in the range of about 0.7 to about 1.3 μm, for example, about 0.8 μm, about 0.9 μm, about 1.0 μm, about 1.1 μm, or about 1.2 μm; the Ni powder preferably has a particle size in the range of about 1.50 to about 2.50 μm, for example, about 1.75 μm, about 2.00 μm, or about 2.25 μm; the WC powder preferably has a particle size in the range of about 0.7 to about 1.3 μm, for example, about 0.8 μm, about 0.9 μm, about 1.0 μm, about 1.1 μm, or about 1.2 μm; The Co powder preferably has a particle size range of about 0.8 to about 1.0 μm, for example, a particle size of about 0.9 μm; and the inhibitor powder preferably has a particle size range of about 1.0 to about 1.5 μm, for example, a particle size of about 1.1 μm, about 1.2 μm, 1.3 μm or about 1.4 μm. Here, each powder as the raw material is preferably within the above-defined particle size range, and the powder within the defined range can make the molded part prepared from the powder have the required mechanical properties.
[0087] The step 2 comprises mixing the mixed powder with a granulating agent in an amount of about 80 to about 100 g per kilogram of the mixed powder, and granulating the mixed powder into granules with a particle size of less than about 150 μm.
[0088] In step 2, the purpose of using a granulating agent is to stabilize the bulk ratio of the mixed powder, improve fluidity, facilitate uniform powder distribution, and effectively reduce the probability of powder segregation and improve product performance stability. In some preferred embodiments, the granulating agent used may include paraffin and / or PEG (polyethylene glycol).
[0089] The amount of the granulating agent used should be in the range of about 80 to about 100 g per kilogram of the mixed powder, such as about 85 g, about 90 g or about 95 g. Here, the amount of the granulating agent should not be too large, such as not exceeding about 100 g per kilogram of the mixed powder, otherwise the difficulty of subsequent removal of the granulating agent increases; nor should it be too small, such as not less than about 80 g per kilogram of the mixed powder, otherwise the desired effect of the granulating agent may not be achieved.
[0090] After the granulating agent and the mixed powder are uniformly mixed, the resulting mixture needs to be granulated into granules with a particle size of less than about 150 μm. Here, for example, the resulting mixture can be sieved through a 100-mesh sieve to form granules, the purpose of which is to make the mixture particles uniform and remove oversized particles.
[0091] The step 3 comprises increasing the temperature of the granules obtained in the step 2 to about 280° C. to about 450° C. at a heating rate of not more than about 3° C. per minute, for example, to remove the granulating agent, and then pre-alloying the granules from which the granulating agent has been removed at a temperature of about 700 to about 1000° C. for about 15 to about 30 minutes.
[0092] Since the granulating agent is not an effective component in the molded part and needs to be removed, in the step 3, the granulating agent in the granules obtained in step 2 is first removed. The granules can be kept at a temperature of about 280 to about 450°C (e.g., about 300°C, about 350°C, or about 400°C) for a period of time to achieve the removal of the granulating agent. Here, the temperature for removing the granulating agent should not be too high, for example, it should not be higher than about 450°C, otherwise the granulating agent may be carbonized, causing carburization of the material; it should not be too low, for example, it should not be lower than about 280°C, otherwise the granulating agent may not be removed completely, and carburization will occur in the material during the subsequent densification and sintering process. In addition, the time for removing the granulating agent is not particularly limited, as long as it can ensure that the granulating agent is completely removed. For example, in a preferred embodiment, the granulating agent removal time is not less than about 60 minutes.
[0093] In step 3, the granules from which the granulating agent has been removed as described above are further pre-alloyed at a temperature of about 700 to about 1000° C. (e.g., about 800° C., about 900° C., or about 960° C.) for about 15 to about 30 minutes. Here, the pre-alloying temperature should not be too high, for example, it should not be higher than about 1000° C., nor should it be too low, for example, it should not be lower than about 700° C.; in addition, the pre-alloying time should not be too long, for example, it should not exceed about 30 minutes, nor should it be too short, for example, it should not be lower than about 15 minutes. Here, on the one hand, if the pre-alloying temperature is too high or the time is too long, the material will not be broken into powder suitable for printing due to sintering; on the other hand, if the pre-alloying temperature is too low or the time is too short, the powder will be too loose and have many pores, which will affect the density of the printed molded part.
[0094] The step 4 comprises crushing and classifying the pre-alloyed particles obtained in the step 3, so as to obtain the titanium carbonitride-based cermet powder having a particle size ranging from about 5 to about 45 μm.
[0095] According to a third aspect of the present invention, the present invention provides a binder jet printing method for preparing a titanium carbonitride-based metal ceramic molded part using the titanium carbonitride-based metal ceramic powder according to the first aspect of the present invention or the titanium carbonitride-based metal ceramic powder prepared according to the preparation method described in the second aspect of the present invention. The specific and preferred features described for the titanium carbonitride-based metal ceramic powder in the first and second aspects of the present invention are also applicable to the third aspect of the present invention.
[0096] The binder jet printing method according to the third aspect of the present invention comprises the following steps a to c.
[0097] The step a comprises printing and shaping the titanium carbonitride-based metal ceramic powder using a binder jet printing process to obtain a printed blank, wherein the powder coating thickness is controlled within a range of about 0.05 to about 0.2 mm.
[0098] In step a, the powder thickness used in the binder jet printing process needs to be controlled within a range of about 0.05 to about 0.2 mm, such as about 0.1 mm or about 0.15 mm. The powder thickness should not be too low, such as not less than about 0.05 mm, otherwise the binder saturation is too high, resulting in low density of the final blank and affecting printing efficiency; nor should it be too high, such as not more than about 0.2 mm, otherwise the binder cannot penetrate and adhere firmly, affecting the strength of the final formed blank.
[0099] In addition, in step a, the binder jetting process may adopt a printing speed commonly used in the art, such as within a range of about 20 to about 45 seconds / layer, such as about 25 seconds / layer, about 30 seconds / layer, about 35 seconds / layer or about 40 seconds / layer. Here, the printing speed should not exceed about 45 seconds / layer, otherwise the printing efficiency is too low; nor should it be less than about 20 seconds / layer, otherwise the dimensional accuracy of the formed blank may be affected.
[0100] In addition, in step a, the binder used in the binder jet printing process is preferably a resin organic binder commonly used in the art, and its viscosity is preferably in the range of about 8 to about 15 cps. In addition, the amount of the binder jetted is about 0.7 to about 1.5 mg / cm 2 within the range.
[0101] The step b comprises curing the printed blank obtained in step a at a temperature of about 80 to about 200° C. for about 3 to about 5 hours to obtain a cured part.
[0102] In the step b, the curing temperature needs to be set in the range of about 80 to about 200° C., for example, about 100° C., about 150° C. or about 180° C. Here, the curing temperature should not be too high, for example, should not exceed about 200° C., otherwise the binder may decompose and fail; nor should it be too low, for example, should not be lower than about 80° C., otherwise the binder cannot be fully cured, resulting in insufficient strength of the blank.
[0103] In addition, the curing time needs to be set within the range of about 3 to about 5 hours, such as about 3.5 hours, about 4 hours or about 4.5 hours. Here, the curing time should not be too long, such as not more than about 5 hours, otherwise the binder may decompose and fail; nor should it be too short, such as not less than about 3 hours, otherwise the binder cannot be fully cured, resulting in insufficient strength of the blank.
[0104] The step c comprises removing the binder from the solidified part obtained in the step b at a temperature of at least about 350° C., and performing pressure liquid phase sintering at a temperature of about 1350 to about 1500° C. and a pressure of about 6 to about 10 MPa for about 30 to about 90 minutes to obtain the titanium carbonitride-based cermet molded part.
[0105] In step c, the binder removal temperature needs to be set at about 350°C or above, such as about 400°C, about 450°C or about 500°C. Here, the binder removal temperature should not be too low, otherwise the binder may not be fully removed. In addition, the binder removal time needs to be set to allow the binder to be fully removed, for example, the binder removal time can be set to at least about 120 minutes.
[0106] In step c, the temperature of the pressurized liquid phase sintering needs to be set in the range of about 1350 to about 1500° C., for example, about 1400° C. or about 1450° C. Here, the temperature of the pressurized liquid phase sintering should not be too high, for example, should not exceed about 1500° C., otherwise the material particles of the sintered blank may grow and be easily deformed; nor should it be too low, for example, should not be lower than about 1350° C., otherwise the densification degree of the blank may be insufficient and the strength may be low.
[0107] In addition, the pressure of the pressurized liquid phase sintering needs to be set above about 6 MPa, such as about 7 MPa, about 8 MPa or about 9 MPa. Here, the pressure of the pressurized liquid phase sintering should not be lower than about 6 MPa, otherwise the density of the molded part is affected.
[0108] In addition, the time of the pressurized liquid phase sintering needs to be set to at least about 30 minutes, such as about 45 minutes, about 60 minutes, about 75 minutes or about 90 minutes. Here, the time of the pressurized liquid phase sintering should not be too short, such as not less than about 30 minutes, otherwise the density of the molded part may be affected.
[0109] According to a fourth aspect of the present invention, the present invention provides a titanium carbonitride-based metal ceramic molded part prepared by the binder jet printing method for preparing a titanium carbonitride-based metal ceramic molded part according to the third aspect of the present invention.
[0110] The titanium carbonitride-based cermet molded part according to the fourth aspect of the present invention has one or more of the following properties:
[0111] Relative density of about 98% or more, Rockwell hardness of about 86 to about 92 HRA, about 1800 N / mm 2 To about 2200N / mm 2 Transverse rupture strength, and length dimension error of less than about 0.15mm per 100mm length.
[0112] The present invention is further described in detail below with reference to specific embodiments.
[0113] All raw materials used in the embodiments of the present invention are commercially available commodities that meet national standards.
[0114] Example 1-5: Preparation of Titanium Carbonitride-Based Metal Ceramic Formed Parts
[0115] (1) Compounding materials:
[0116] Weigh each raw material according to the ratio listed in Table 1, wherein the Feerg size of Ti(C,N) powder is in the range of about 1.50 to about 2.50 μm, the particle size of WC powder is in the range of about 0.7 to about 1.3 μm, the particle size of Ni powder is in the range of about 2.2 to about 2.8 μm, the particle size of Co powder is in the range of about 0.8 to about 1.0 μm, and the particle size of inhibitor powder is in the range of about 1.0 to about 1.5 μm. After mixing each raw material, ball milling treatment is performed by ball milling wet mixing process to make them fully and evenly mixed. In the ball milling wet mixing process, the ball milling medium is alcohol, the grinding ball is a cemented carbide ball with a diameter of about 9 mm, the ball-to-material ratio (weight ratio) is about 7:1, and the ball milling time is about 30 hours. Then the obtained ball milled titanium carbonitride-based cermet powder is dried at a temperature of about 80°C and passed through a 60-mesh sieve.
[0117] (2) Powder granulation:
[0118] Add a granulating agent to the powder obtained in the above step (1), wherein the addition ratio of the granulating agent is about 90 g per kg of the powder. After the powder and the granulating agent are kneaded and mixed evenly, the powder is passed through a 100-mesh sieve to prepare a granular material.
[0119] (3) Pre-alloying:
[0120] The granules obtained in step (2) are heated to about 400° C. at a heating rate of less than about 3° C. / min and kept at this temperature for at least about 1 hour to remove the granulating agent, and then the granules from which the granulating agent has been removed are subjected to a pre-alloying treatment, wherein the temperature of the pre-alloying treatment is about 960° C. and the time is not less than about 15 minutes but not more than about 30 minutes.
[0121] (4) Crushing and Classification
[0122] The granular material obtained in step (3) is crushed and classified to obtain a titanium carbonitride-based cermet powder having a particle size ranging from about 5 to about 45 μm.
[0123] (5) Binder jet printing:
[0124] The titanium carbonitride-based metal ceramic powder obtained in the above step (4) is printed and formed using a binder injection molding device. According to the pre-designed special-shaped part graphic structure, the powder to be printed is placed in a powder container, and is spread on the workbench in the printing area at a powder thickness of about 0.1 mm and a printing rate of about 25 seconds / layer. Through the injection and solidification of the binder, multi-layer powder distribution and re-injection, a blank of a specified shape is obtained, wherein the binder used is a resin organic binder with a viscosity of about 10 cps, and the amount of the binder sprayed is about 1.0 mg / cm 2 The size accuracy of the blank is controlled to be less than about ±0.15mm per 100mm.
[0125] (6) Curing:
[0126] The blank obtained in the above step (5) is subjected to a curing treatment, wherein the curing temperature is about 180° C. and the curing time is about 4 hours. After the curing is completed, the unformed powder is swept away to obtain a cured part.
[0127] (7) Binder removal and sintering:
[0128] The solidified part obtained from the above step (4) is kept at a temperature of about 380°C for about 120 minutes to remove the binder, and then treated by degreasing-pressurizing liquid phase sintering to obtain the titanium carbonitride-based metal ceramic molded part, wherein the sintering temperature is about 1450°C, the holding time is about 45 minutes, and the pressurization pressure is about 10Mpa.
[0129] Table 1:
[0130]
[0131] According to the relevant provisions of the Chinese national standards GB / T 3850-2015 "Dense Sintered Metal Materials and Cemented Carbide Density Determination Method", GB / T 3849.1-2015 "Cemented Carbide Rockwell Hardness (A Scale) Test Method" and GB / T 3851-2015 "Cemented Carbide Transverse Fracture Strength Determination Method", the titanium carbonitride-based cermet molded parts obtained from the above Examples 1 to 5 were sampled and performance tested and analyzed, and the length dimension error per 100 mm was measured. The performance test results are shown in Table 2 below. The relative density in Table 2 refers to the percentage of the density measured by the national standard GB / T 3850-2015 relative to the theoretical density.
[0132] Table 2:
[0133]
[0134] From the data in Table 2 above, we can see that:
[0135] By adopting the embodiment of the present invention, a binder jetting technology can be used for 3D printing and after sintering and densification, a relative density of about 98% or more, a Rockwell hardness in the range of about 86 to about 92 HRA, and a transverse rupture strength of about 1800 N / mm 2 To about 2200N / mm 2 Titanium carbonitride-based cermets within the range of 100 mm in length are controlled within 0.15 mm. In addition, by adjusting the proportions of the components, materials with different gradient properties can be achieved to meet various performance requirements, and complex shaped parts can be formed by 3D printing with binder jetting.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A titanium carbonitride-based metal ceramic powder that can be used for 3D printing, characterized in that: The titanium carbonitride-based metal ceramic powder comprises, based on the total weight of the metal ceramic powder: 70 to 90 wt % of a hard phase comprising a Ti(C,N) matrix and a WC reinforcement phase; 9 to 27 wt. % Ni and / or Co binder phase, and 1 to 3% by weight of an inhibitor, The particle size of the titanium carbonitride-based metal ceramic powder is in the range of 5 to 45 μm.
2. The titanium carbonitride-based metal ceramic powder according to claim 1, characterized in that: The titanium carbonitride-based cermet powder comprises 55 to 65 wt % of a Ti(C,N) matrix and 15 to 25 wt % of a WC reinforcement phase as the hard phase, based on the total weight of the cermet powder; and / or The titanium carbonitride-based cermet powder comprises 10 to 20 wt % of the Ni and / or Co binder phase based on the total weight of the cermet powder.
3. The titanium carbonitride-based metal ceramic powder according to claim 1 or 2, characterized in that: The Ti(C,N) matrix comprises Ti(C x ,N 1-x ) matrix, wherein x = 0.1 to 0.9; and / or The inhibitor comprises TaC, TiC, Cr3C2 and / or VC.
4. A method for preparing the titanium carbonitride-based metal ceramic powder according to any one of claims 1 to 3, characterized in that: The method comprises: Step 1: providing a mixed powder, and optionally subjecting the mixed powder to a grinding process, wherein the mixed powder comprises, based on the total weight of the mixed powder: 70 to 90 wt. % of hard phase powder, the hard phase powder comprising Ti(C,N) powder and WC powder, 9 to 27 wt% Ni and / or Co powder, and 1 to 3 wt% inhibitor powder; Step 2: uniformly mixing the mixed powder with the granulating agent in an amount of 80 to 100 g per kilogram of the mixed powder, and granulating to form granules with a particle size of less than 150 μm; Step 3: keeping the granules obtained in step 2 at a temperature of 280° C. to 450° C. to remove the granulating agent, and then pre-alloying the granules from which the granulating agent has been removed at a temperature of 700 to 1000° C. for 15 to 30 minutes; and Step 4: crushing and classifying the pre-alloyed particles obtained in step 3 to obtain the titanium carbonitride-based cermet powder with a particle size ranging from 5 to 45 μm.
5. The preparation method according to claim 4, characterized in that: The mixed powder in step 1 comprises, based on the total weight of the mixed powder: 55 to 65 wt% Ti(C,N) powder, 15 to 25 wt.% WC powder, 10 to 20 wt% Ni and / or Co powder, and 1 to 3 wt% inhibitor powder.
6. The preparation method according to claim 4 or 5, characterized in that: The Ti(C,N) powder has a Fisher particle size in the range of 1.50 to 2.50 μm; and / or The WC powder has a particle size range of 0.7 to 1.3 μm; and / or The Ni powder has a particle size range of 2.2 to 2.8 μm; and / or The Co powder has a particle size range of 0.8 to 1.0 μm; and / or The inhibitor powder has a particle size range of 1.0 to 1.5 μm.
7. The preparation method according to claim 4 or 5, characterized in that: The granulating agent comprises paraffin and / or polyethylene glycol.
8. A binder jet printing method for preparing a titanium carbonitride-based metal ceramic molded part using the titanium carbonitride-based metal ceramic powder according to any one of claims 1 to 3, characterized in that: The method comprises: Step a: using a binder jet printing process, jet-printing the titanium carbonitride-based metal ceramic powder to obtain a printed blank, wherein the powder coating thickness is in the range of 0.05 to 0.2 mm; Step b: curing the printed blank obtained in step a at a temperature of 80 to 200° C. for 3 to 5 hours to obtain a cured part; Step c: keeping the solidified part obtained in step b at a temperature of at least 350°C to remove the binder, and performing pressure liquid phase sintering at a temperature of 1350 to 1500°C and a pressure of at least 6 MPa for 30 to 90 minutes to obtain the titanium carbonitride-based metal ceramic molded part.
9. The binder jet printing method according to claim 8, characterized in that: The binder jet printing process of step a uses a resinous organic binder with a viscosity in the range of 8 to 15 cps and a binder with a viscosity in the range of 0.7 to 1.5 mg / cm 2 The amount of binder sprayed.
10. A titanium carbonitride-based metal ceramic molded part prepared by the binder jet printing method according to claim 8 or 9, characterized in that: The molded part has one or more of the following properties: Relative density above 98%, Rockwell hardness of 86 to 92 HRA, 1800N / mm 2 Up to 2200N / mm 2 The transverse rupture strength, and The length dimension error is less than 0.15mm per 100mm length.